Sulfated Polysaccharide Anticoagulants Suppress Natural Killer Cell Activity In Vitro - Johann, Sabine; Zoller, Christine; Haas, Sylvia; Blümel, Günther; Lipp, Martin; Förster, Reinhold (Thrombosis and Haemostasis, 1995)
In contrast to the well studied anticoagulant activity of sulfated polysaccharides (SPS), little is known about their influence on immune competent cells. Using two naturally derived SPSs (unfractionated heparin and low molecular weight heparin), one semi-synthetic SPS (pentosanpolysulfate), and one synthetic SPS (lactobionic acid) as well as the polypeptide hirudin we investigated the effect of these drugs on natural killer cell activity in vitro. We demonstrate that all SPSs tested significantly suppress the activity of natural killer cells at clinically relevant dosages. At all concentrations and at all effector:target ratios tested pentosanpolysulfate was the most potent natural killer cell inhibitor. In contrast, hirudin had no effect on natural killer cell function. Furthermore, scanning electron microscopy revealed that reduced natural killer cell activity is paralleled by decreased lymphocyte cell size and altered cell surface structures. Our results indicate that defined therapeutically applied SPSs can interfere with the tumor cell killing process.